A comparative interrupted time-series assessing the impact of the Armstrong decision on officer-involved shootings. (3rd September 2022) - Boehme, Hunter M.; Kaminski, Robert J.; Leasure, Peter
ABSTRACT: In the 2016 case of Estate of Armstrong V. The Village of Pinehurst (Armstrong ), the Fourth Circuit Court decided to significantly restrict CED use to only encounters that pose an 'immediate safety risk' or 'immediate danger.' Some authors have argued that the decision from Armstrong could lead to increased officer-involved shootings. The present study tests this prediction by utilizing a comparative interrupted time-series analysis. Findings from time-series count models show statistically significant increases in monthly and weekly officer-involved shootings (OISs) within the Fourth Circuit, and statistically significant decreases in weekly OISs among states comparable to, but outside the Fourth Circuit's jurisdiction. Policy implications of these findings are discussed in detail.